Sistem Informasi Penjualan Bahan Baku Pembuatan Speedboat Berbasis Website PD. Standard Fiber Glass Pontianak - Reza Maulana; Yulia Yulia; Anastasia Anastasia (Jurnal Sistem Komputer dan Informatika (JSON), 2021)
In today's era of globalization, information technology is accelerating. As for computers that are equipment created to facilitate human work, when achieving progress in both hardware and software manufacturing. PD. Standard Fiber Glass requires the existence of an information system that supports and provides satisfactory service for customers. That's why the author tried to create the Final Task regarding the raw material sales system of making speedboats in PD. Standard Fiber Glass that until now has not been computerized PD. Standard Fiber Glass is only a company engaged in commerce. The system is in the PD. Standard Fiber Glass is still done manually, ranging from recording transactions, to storing other data related to the sales process to the creation of reports, so that it is possible that during the process there are errors in recording, less accurate reports are made. The design of this information system is the best solution to solve the problems that exist in this company, and with a computerized system can be achieved an effective and efficient activity in supporting activities in this company.